2000
DOI: 10.1021/la991408g
|View full text |Cite
|
Sign up to set email alerts
|

The Bending Elasticity of 1-Monoolein upon Relief of Packing Stress

Abstract: The bending elasticity of the monoglyceride 1-monoolein (MO) in water has been measured in the inverse hexagonal (HII) phase at 37 °C. At this temperature, fully hydrated MO is normally in an inverse bicontinuous cubic phase based on Schwarz's D surface, . The addition of either of the C23 chainlength hydrocarbons, tricosane or 9-cis-tricosene, at mole fractions with respect to MO in excess of 0.05, induces a phase transition into the HII phase. This transition is understood to occur because packing stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…In fact, temperature is known to dramatically influence the phase behavior, final curvature and fluidity of lipids in the absence of DNA [21,22], and those effects can be easily translated to the properties of the lipoplex itself. In the case of pDNA:DODAB:MO lipoplexes, where DODAB assumes the role of the bilayer-forming cationic lipid with an high melting temperature (T M = 45 • C) [23,24] and MO the role of the nonlamellar-forming neutral surfactant with a low melting temperature (T M = 32 • C) [25,26], as well as the molar fraction of both constituents is expected to strongly influence the physicochemical properties and structure of the final lipoplex, as previously observed in the absence of nucleic acids [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, temperature is known to dramatically influence the phase behavior, final curvature and fluidity of lipids in the absence of DNA [21,22], and those effects can be easily translated to the properties of the lipoplex itself. In the case of pDNA:DODAB:MO lipoplexes, where DODAB assumes the role of the bilayer-forming cationic lipid with an high melting temperature (T M = 45 • C) [23,24] and MO the role of the nonlamellar-forming neutral surfactant with a low melting temperature (T M = 32 • C) [25,26], as well as the molar fraction of both constituents is expected to strongly influence the physicochemical properties and structure of the final lipoplex, as previously observed in the absence of nucleic acids [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…MO is a natural-occurring neutral surfactant that has the particularity of forming two inverted bicontinuous cubic phases (QII D and QII G ) in excess water [61,62]. It possesses a single unsaturated acyl chain (C18:1) attached to a glycerol headgroup [63]. Its tendency to form inverted bicontinuous cubic phases has been explored in the past for different applications such as protein crystallization [64,65] or matrix for gel electrophoresis [66], and justifies the structural richness of the liposomal system formed with DODAB [40].…”
Section: Introductionmentioning
confidence: 99%
“…The driving force for the formation of the cubic phase in hydrated monoolein comes from the tendency of monoolein to curl away from the planar lamellar phase. This tendency can be expressed as the curvature elastic energy function [40,41] . Our findings, however, demonstrated that DHP107 did not form a cubic phase.…”
Section: Discussionmentioning
confidence: 99%